(untitled) (Physical Education, Health and Social Sciences, 2026)
Musculoskeletal problems are described as muscular pain, discomfort, numbness and ache to the support system of the human body it can occur due to different causative factors like excessive forces, repetitive movement on the joints and constantly sustaining same position. To determine the comparative impact of various electronic devices on the musculoskeletal health status among Medical and Physical Therapy students. A cross-sectional study having 377 undergraduate medical and physical therapy students from different institute of Karachi. A self-administrated questionnaire adopted from Woo et.al was distributed among students who fulfilled the criteria. Data was coded and confidentiality was maintained. The result shows that the high prevalence of musculoskeletal problem in mobile phone user (98%), laptop user (61%) and least in which devices uses in least amount desktop computer (23.3%), tablet computer (18.5%) and game console (16.4%). The study concludes that the prolong use of electronic devices impact the musculoskeletal health specially in mobile phone and laptop user.